Usefulness of Magnifying Endoscopy with Narrow-Band Imaging for Determining Tumor Invasion Depth in Early Gastric Cancer - Daisuke Kikuchi; Toshiro Iizuka; Shu Hoteya; Akihiro Yamada; Tsukasa Furuhata; Satoshi Yamashita; Kaoru Domon; Masanori Nakamura; Akira Matsui; Toshifumi Mitani; Osamu Ogawa; Sumio Watanabe; et al. (Gastroenterology Research and Practice)
Backgrounds. Magnifying endoscopy with narrow-band imaging (ME-NBI) has become essential for determining tumor margin in early gastric cancer (EGC). Here, we investigated the usefulness of ME-NBI for assessment of invasion depth in EGC. Methods. For 119 patients who had undergone ME-NBI and en bloc resection by endoscopic submucosal dissection, three physicians prospectively examined high-magnification ME-NBI images for clinical features such as presence or absence of dilated vessels (D vessels). Cases with D vessels verified by at least two physicians were assigned to group V, and others were assigned to group N. We then compared clinicopathological factors associated with the groups. Results. Groups V and N consisted of 18 and 101 patients, respectively. There were no significant differences in age, gender, tumor size, tumor location, gross morphology, or histological type. The percentage of submucosal cancer was 9.9% (10/101) in group N and significantly higher at 33.3% (6/18) in group V (). When the presence of D vessels was considered a diagnostic criterion for submucosal cancer, diagnostic accuracy, sensitivity, and specificity were 81.5, 37.5, and 88.3%, respectively. Conclusions. The results suggest that identification of D vessels using ME-NBI can assist in the assessment of invasion depth in EGC.